2006
DOI: 10.1177/0957926506062358
|View full text |Cite
|
Sign up to set email alerts
|

Life stories used as evidence for the diagnosis of addiction in group therapy

Abstract: In this article I study how the life stories of patients are used as evidence in the diagnosis of addiction in Minnesota model group therapy. As part of this therapy, patients have to tell their life story, concentrating on their substance abuse. This story is used by the therapists as a means for getting patients to recognize and accept that they are addicts. For this purpose the therapists use intervening questions. This article concentrates on the placement and the structure of the patients’ responses to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Turning to Eddie, while our reading of Eddie's interview suggests that he constructed himself as the object of power relations of the sort identified by Halonen (2006), it is significant that Eddie was nonetheless able to construct himself as able to exercise agency and self-determination by choosing to drink alcohol and continue attending NA meetings. If AA/NA was a genuinely totalising discourse, it is hard to see how the subject would be able to step out of it.…”
Section: Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…Turning to Eddie, while our reading of Eddie's interview suggests that he constructed himself as the object of power relations of the sort identified by Halonen (2006), it is significant that Eddie was nonetheless able to construct himself as able to exercise agency and self-determination by choosing to drink alcohol and continue attending NA meetings. If AA/NA was a genuinely totalising discourse, it is hard to see how the subject would be able to step out of it.…”
Section: Resistancementioning
confidence: 98%
“…These critiques have variously accused AA of being a cult (Alexander and Rollins, 1984), of inflating its claimed success rate (Peele, 1989), and of coercing and indoctrinating its members (Bufe, 1997). Some academic studies have argued that AA's conventions for sharing life stories subjugate agency through their tendency to reconstruct members' narratives of identity in ways aligned with AA norms (Warhol and Michie, 1996;Halonen, 2006). Documentary analysis of AA texts has tended to portray AA as an oppressive regime (Keane, 2000;Reith, 2004).…”
mentioning
confidence: 99%
“…The other function is that of assessment, where life stories are used as a diagnostic tool to collect relevant information to find out about or to check on someone's physical or mental state. Halonen (2006) showed that life stories are used as evidence for assessing addiction. In this research, therapists used yes/no questions to establish facts, such as about "increased drinking" and "loss of control", in order to arrive at a diagnosis and to confront the patient with being an addict (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies are consistent with this finding (Antaki, 2008;Antaki, Barnes and Leudar, 2005;Peräkylä, 2004;Vehviläinen, 2003). On the other hand, formulations have been shown to be appropriate devices for the purposes of history-taking, selecting a candidate problem and establishing it as therapeutically relevant (Antaki et al, 2005;Davis, 1986;Hak and de Boer, 1996;Halonen, 2006;Vehviläinen, 2003). Formulations, also, have been described to be employed by patients to elaborate on the therapist's interpretations (Peräkylä, 2005).…”
Section: Using Formulations To Transform the Patient's Avowalsmentioning
confidence: 70%